Sources and source areas of the Upper Paleozoic metasedimentary rocks of the Dzhagda terrane of the Mongol-Okhotsk fold belt: the results of Sm-Nd isotope geochemical studies - V. A. Zaika; A. A. Sorokin; V. P. Kovach (Геодинамика и тектонофизика, 2018)
The article presents the results of Sm-Nd isotope geochemical studies of the Upper Paleozoic metasedimentary rocks of the Dzheskogon, Nektera and Bochagor suites of the Dzhagda terrane. These rocks are characterized by slightly varying values of the Nd model age tNd(DM)=1.5–1.0 Gyr, which gives evidence that the main sources of protoliths were the rocks of the Mesoproterozoic Nd model age (in average). This Nd model age is similar to the ages of the metaterrigenous rocks of the Teply Klyuch, Garmakan and Alga suites of the Tukuringra terrane of the Mongol-Okhotsk Belt. The results obtained in our studies suggest that the sedimentary rocks of the Dzhagda and Tukuringra terranes developed from the material that was mainly sourced from the Amur superterrane (from the south in modern coordinates). A supply of the material from the southern margin of the North Asian craton (from the north in modern coordinates) was either absent or minimal.